Epidemiology of cryptococcosis in Malaysia - Tay, S.T.; Rohani, M.Y.; Soo Hoo, T.S.; Hamimah, H. (2010)
This study describes the isolation of Cryptococcus neoformans and Cryptococcus gattii from patients with chronic meningitis who were admitted to 16 Malaysian hospitals, from 2003 to 2004. Of the 96 cryptococcal cases reported over the 2-year period, 74 (77.1) patients were male and 45 (46.9) patients were between 30 and 39 years old. Cryptococcosis was uncommon in children. A total of 57 (59.4) and 23 (24.0) patients were Malay and Chinese respectively. Human immunodeficiency virus infection was the major underlying disease reported in 36 (37.5) patients. C. neoformans var. grubii (serotype A and molecular type VNI) was the predominant Cryptococcus species isolated from 88.5 of cryptococcal cases in this country. Cryptococcal cases due to C. neoformans var. grubii were reported from all the five regions in Malaysia, with the most number of cases reported from the central and northern regions. Cryptococcus gattii (all were serotype B and molecular types VGI/II) was isolated from all regions except the southern region. Compared with a study conducted prior to the AIDS era, our findings show substantial changes in the demographical characteristics of patients.